Effect of Level of Protein on Digestibility and Nitrogen Balance in Sudan Desert Sheep Fed Molasses-Based Fattening Rations (University of Khartoum Journal of Agricultural Sciences, 2023)
Three yearling intact males of Sudan desert sheep (Hamariecotype) ranging in weight between 26 and 30 kg were used in a 3x3 latinsquare design with the objective of studying the effect of feeding threecrude protein (CP) levels (14.5%, 16.7% and 18.7%) in complete iso-caloric molasses-based diets on nitrogen-balance, digestibility ofnutrients, rectal temperature and respiration rate. Nitrogen (N) level hadno significant effect on the digestibility coefficients of the differentnutrients, total digestible nutrients (TDN) and N-balance. Urine volume,rectal temperature and respiration rate were not affected by N level.